Contribution of CD4+ cells in the emotional alterations induced by endometriosis in mice - Escudero-Lara, Alejandra; Cabañero, David; Maldonado, Rafael (Frontiers in Behavioral Neuroscience, 2022)
Endometriosis is a disease defined by the presence of endometrial tissue in extrauterine locations. This chronic condition is frequently associated with pain and emotional disorders and has been related with altered immune function. However, the specific involvement of immune cells in pain and behavioral symptoms of endometriosis has not been yet elucidated. Here, we implement a mouse model of nonsurgical endometriosis in which immunocompetent mice develop abdomino-pelvic hypersensitivity, cognitive deficits, anxiety and depressive-like behaviors. This behavioral phenotype correlates with expression of inflammatory markers in the brain, including the immune cell marker CD4. Depletion of CD4+ cells decreases the anxiety-like behavior of mice subjected to the endometriosis model, whereas abdomino-pelvic hypersensitivity, depressive-like behavior and cognitive deficits remain unaltered. The present data reveal the involvement of the immune response characterized by CD4+ white blood cells in the anxiety-like behavior induced by endometriosis in mice. This model, which recapitulates the symptoms of human endometriosis, may be a useful tool to study the immune mechanisms involved in pain and behavioral alterations associated to endometriosis.